Teachers' Desired Mobility to Disadvantaged Schools: Do Financial Incentives Matter? - Julien Silhol; Lionel Wilner (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper exploits a 2018 reform of teachers' financial incentives to work in some French disadvantaged schools. Based on this quasi-natural experiment, it evaluates the impact of those incentives on teachers' stated preferences to move to such schools. Using data from the internal human resource management of some educational authority, we find that most responsive teachers have less experience and work already in those areas. Counterfactual simulations suggest that the policy has not hurt other disadvantaged schools, but rather induced some teachers not to remain in their current school or to opt less for regular schools.
Keywords: I21; I22; J45; 330; teacher mobility; financial incentives; stated preferences; rank-ordered choices; disadvantaged schools